2021
DOI: 10.1007/s10639-021-10557-5
|View full text |Cite
|
Sign up to set email alerts
|

Examining university students’ behavioural intention to use e-learning during the COVID-19 pandemic: An extended TAM model

Abstract: This present study aims to investigate factors that impact behavioural intention of university students on e-learning use during the COVID-19 pandemic. An online questionnaire was utilised to gather data from 109 students enrolled in one of the universities in Indonesia. The Technology Acceptance Model (TAM) was the primary framework employed for analysis, in which system quality and e-learning experience were included as external constructs to seek out a much better model to improve the understanding of stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
173
0
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(223 citation statements)
references
References 64 publications
33
173
0
17
Order By: Relevance
“…Several studies were conducted to determine the factors that are expected to have an effect on students' remote emergency learning experience (Tanveer et al, 2020;Mailizar et al, 2021;Gopal et al, 2021;Almaiah et al, 2020;Sharma & Alvi, 2021;Almossa, 2021).The Community of Inquiry and Acceptance model is a widely used model in studies of learning environments' impact on student's cognitive process. This model was extended in several previous studies to examine factors related to variant modes of online and blended learning.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Several studies were conducted to determine the factors that are expected to have an effect on students' remote emergency learning experience (Tanveer et al, 2020;Mailizar et al, 2021;Gopal et al, 2021;Almaiah et al, 2020;Sharma & Alvi, 2021;Almossa, 2021).The Community of Inquiry and Acceptance model is a widely used model in studies of learning environments' impact on student's cognitive process. This model was extended in several previous studies to examine factors related to variant modes of online and blended learning.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In accordance with the above, it is evident that there are more researchers who have used Subjective Norm, for example [59], [78], [82], [83], [1], [26], [85], [86], [87], [88], [89], [90], [91], [92], Experience in the internet & computer [59], [77], [81], [82], [84], [85], [93], [94], [95], [96], [97] Self-Efficacy [59], [83], [84], [85], [1], [71], [72], [73], [86], [95], [98], [99], [74], [97], Technical Support [59], [42], [73], [74], [83], [100], [101], [102] and Anxiety [72], [73],…”
Section: External Variables Of Tammentioning
confidence: 99%
“…Researchers [96], [97], [122] emphasized that Experience in the internet and Computer has no significant impact on Perceived Usefulness while other researchers [59], [76], [82], [94], [95], [123] identified that Experience in the internet and computer has a significantly impact on Perceived Usefulness further confirmed that Experience in the internet and Computer has a significant positive impact on the Perceived Usefulness [76], [82], [94], [95], [123] while researcher [59] found that Experience in the internet and Computer has a significant negative impact on the Perceived Usefulness.…”
Section: Experience In the Internet And Computermentioning
confidence: 99%
See 1 more Smart Citation
“…TAM's popularity was demonstrated by the number of articles and introductory papers [41] and [42]. [53], [69], [70], [57], [71], [61], [72][73][74][75][76] Self-Efficacy [35], [53], [58], [71], [61], [59], [55], [77], [78], [62], [74], [79][80][81], [76], Technical Support [35], [53], [29], [78], [81], [58], [82], [83], [84] and Anxiety [35], [77], [78], [69], [71], [61], [76], [85][86] [42]. There is a significant impact, so it is once Subjective Norm's collaboration was incorporated into the new model to examine a link between behavioral intention and social influence [36], [42].…”
Section: The Technology Acceptance Model (Tam)mentioning
confidence: 99%